2017
DOI: 10.3399/bjgp17x688861
|View full text |Cite
|
Sign up to set email alerts
|

GP views on strategies to cope with increasing workload: a qualitative interview study

Abstract: BackgroundThe existence of a crisis in primary care in the UK is in little doubt. GP morale and job satisfaction are low, and workload is increasing. In this challenging context, finding ways for GPs to manage that workload is imperative.AimTo explore what existing or potential strategies are described by GPs for dealing with their workload, and their views on the relative merits of each.Design and settingSemi-structured, qualitative interviews with GPs working within NHS England.MethodAll GPs working within N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 7 publications
1
81
0
2
Order By: Relevance
“…Data on GP strategies for dealing with workload are published in a separate, accompanying article. 17 Participants' descriptions of workload Most participants described long, intense days spent in general practice. Typical working days ranged from 10-14 hours, often with little or no time for breaks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on GP strategies for dealing with workload are published in a separate, accompanying article. 17 Participants' descriptions of workload Most participants described long, intense days spent in general practice. Typical working days ranged from 10-14 hours, often with little or no time for breaks.…”
Section: Resultsmentioning
confidence: 99%
“…Difficulty recruiting doctors, lack of a solution provided by locums, and the financial pressures on practices further indicate that coping strategies are presently limited (the authors' accompanying article on GPs' suggestions for strategies to cope with increasing workload is published alongside this article). 17 The unattractiveness of partnership is particularly worrying because these positions are mainly occupied by the most experienced GPs who are in the best position to be able to retire.…”
Section: Implications For Practicementioning
confidence: 99%
“…Existing qualitative work has tended to use smaller samples. 6,21,22 or examine the experiences of GPs in different parts of the world. 17 The study aimed to address these limitations by eliciting a larger group of English GPs' feelings concerning what helps and hinders them in receiving support for their chronic stress or distress, hence giving greater weight to the intrinsic, rather than extrinsic, value of GP wellbeing.…”
Section: Methodsmentioning
confidence: 99%
“…24,39 A recent article found that many GPs have reduced their sessions in order to cope with the stress of an increasing workload. 22 These findings build on this by adding detail to the ways in which GPs might vary their working days or assert their boundaries, demonstrating ways in which individual GPs may protect themselves within the current general practice structure. However, while these may be beneficial strategies for the individual, they could have damaging consequences for patients and the profession unless there are resources available to recruit more GPs.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation